Advances in Streamflow Forecasting: From Traditional to Modern Approaches - Sharma, Priyanka; Machiwal, Deepesh (Elsevier, 2021)
Advances in Streamflow Forecasting: From Traditional to Modern Approaches covers the three major data-driven approaches of streamflow forecasting including traditional approach of statistical and stochastic time-series modelling with their recent developments, stand-alone data-driven approach such as artificial intelligence techniques, and modern.